Relationship Between Attitudes toward E-Learning Method and Learning Achievement in English Language Study Program Students at FKIP UMSU - Ratna Sari Dewi; Selamat Husni Hasibuan (BIRCU, 2019)
The purpose of this study was to determine the relationship between student attitudes towards the E-Learning method and the learning achievement of English Language Education students at North Sumatra Muhammadiyah University. This research was conducted at UMSU with the subject of English Language Education Semester VIII. Data collection in this study was conducted using a questionnaire and documentation study. Questionnaires are used to collect data on student attitudes in online learning, while documentation studies are used to collect data on student learning outcomes. The technique used in this study is to test the validity and reliability. Data processing techniques use the SPSS version 20 program by carrying out tests of normality and linearity. The results of the linearity test at a significance level of 0.007 <0.05 which indicates the relationship between the attitude of e-learning learning and learning achievement is linear. between the attitude of students towards E-Learning learning with learning achievement in the English study program UMSU.